Risk Preferences in Participative Budgeting - Kim, D. C. (The Accounting Review, 1992)
[This study examines participative budgeting in the context of the psychology of risk. As Young (1985) and Waller (1988) report, there is some preliminary evidence that risk-averse workers create more budgetary slack than risk-neutral ones. They show that "truth inducing incentive schemes" (e.g., Soviet incentive schemes; see Weitzman 1976) reduce budgetary slack for risk-neutral subjects but not for risk-averse subjects. If this is true, it means that resource allocations within organizations are mediated by perceptions of risk. Young (1985) and Waller (1988) define risk preference as a dispositional variable, which presumes that it is a stable personal trait, a latent variable, traditionally inferred from observed behavior of risk propensity in such settings like lotteries. This study tests whether risk preferences are domain-specific; that is, latent risk preferences translate into differing manifest risk preferences according to the context. Domain-specific risk preference can be understood as a manifest psychological variable that may well be the result of the combination of latent risk propensity and the situation. Kahneman and Tversky's prospect theory (1979) suggests that manifest risk preferences depend upon whether the subject frames his or her task in the context of gain or loss prospects, where gains and losses are defined in relation to a neutral reference point. If risk preferences are domain-specific, then past studies' suggestion that incentive schemes should be designed in consideration of dispositional, or latent, risk preferences needs to be reexamined (Waller 1988; Kaplan 1982). The question before this study is: If subordinates are influenced by prior period performance in setting current period budgets for themselves, will that influence take the form predicted by prospect theory and thus lead to riskier preferences (tight budgets) when the subordinates perceive themselves in a losing situation? This is an important question considering Young's (1985) alluding to the possibility that inducing subordinates to less risk-averse behavior may be a way to favor tight budgetary standards and reduce slack. This prediction is consistent with prospect theory's implication that losers who are slow to adjust their reference point act in a more risk-seeking manner. Thus, the induction of losing prospects might be a way to minimize budgetary slack. An additional concern in this study is to jointly test domain-specific risk preferences and dispositions toward risk as influences over budgetary decisions. Whereas prospect theory explains risk preferences as domain-specific contingencies, other theories construe risk preferences as dispositional. It is likely that both domain-specific and dispositional factors influence budgetary decisions. This study deploys a conventional lottery procedure to elicit and test dispositions toward risk. An experiment simulating the public accountants' budgeting of billable hours was designed to test the hypothesis that subject preference for tight or safe budget behavior depends on the performance of coworkers and domain-specific risk preferences. The hypotheses were tested in an experiment employing 81 students. The results generally support the view that subordinates' risk preferences are influenced by a situation-dependent variable. The reversal of risk preferences around a neutral reference point is statistically significant for both dispositionally risk-averse and dispositionally risk-seeking subjects. The dispositional variable also contributes to the explanation of variations in subjects' manifest risk preferences. Thus the propensity to induce budgetary slack seems to be a joint function of situations and dispositions.]